2022
DOI: 10.3390/v14091901
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of a Reassortant 2.3.4.4b Highly Pathogenic H5N1 Avian Influenza Virus Containing H9N2 PA Gene in Burkina Faso, West Africa, in 2021

Abstract: Since 2006, the poultry population in Burkina Faso has been seriously hit by different waves of Highly Pathogenic Avian Influenza (HPAI) H5N1 epizootics. In December 2021, three distinct regions of Burkina Faso, namely, Gomboussougou, Bonyollo, and Koubri, detected HPAI H5N1 viruses in poultry. Whole genome characterization and statistical phylogenetic approaches were applied to shed light on the potential origin of these viruses and estimate the time of virus emergence. Our results revealed that the HPAI H5N1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…The absence of substitutional mutations at amino acid positions 26, 30, 31, and 34 within the M2 sequence indicated no genetic markers related to the resistance to amantadine. The NS1 PDZ motif ESEV (227-230) was found in the Egyptian H5N1 isolate, which is typically shown in HPAI-H5N1, with no deletion in the NS1 of the strain under study (Table 2), as previously reported in the West African H5N1 strains of clade 2.3.4.4 [21]. However, the A/Ibis/Egypt/RLQP/229S/2022 isolate carries mammalian adaption and virulence traits such as PB2 (504V), PB1 (13P and 598L), PB1-F2 (82S), PA (127V, 672L, and 550L), NP (398Q), M2 (64S), and NS1 (42S).…”
Section: Genetic Characterization Revealed Close Related Features To ...supporting
confidence: 76%
See 1 more Smart Citation
“…The absence of substitutional mutations at amino acid positions 26, 30, 31, and 34 within the M2 sequence indicated no genetic markers related to the resistance to amantadine. The NS1 PDZ motif ESEV (227-230) was found in the Egyptian H5N1 isolate, which is typically shown in HPAI-H5N1, with no deletion in the NS1 of the strain under study (Table 2), as previously reported in the West African H5N1 strains of clade 2.3.4.4 [21]. However, the A/Ibis/Egypt/RLQP/229S/2022 isolate carries mammalian adaption and virulence traits such as PB2 (504V), PB1 (13P and 598L), PB1-F2 (82S), PA (127V, 672L, and 550L), NP (398Q), M2 (64S), and NS1 (42S).…”
Section: Genetic Characterization Revealed Close Related Features To ...supporting
confidence: 76%
“…A new wave was observed in 2016–2017 by a novel reassortant of H5N8 and H5N5 of clade 2.3.4.4b and resulted in the death of millions of birds in several countries worldwide [ 18 ]. Recently, in late 2020, different genotypes of HPAI H5N1 within clade 2.3.4.4b have emerged in wild birds and were detected in several countries in Africa, Asia, Europe, and North America [ 19 , 20 , 21 , 22 ], which led to the death of over 70 million birds [ 21 , 23 ]. During natural circulation, the HA gene of the HPAI H5N8 clade 2.3.4.4b reassorted with four different low pathogenic viruses to produce the recent H5N1 virus, which then reassorted with other distinctive AIV variants and generated at least 15 different H5N1 genotypes [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…M, Nucleoprotein (NP), nuclear export protein (NEP), non-structural 1 proteins (NS1) polymerase basic protein 1 (PB1) and PB1-F2, polymerase basic protein 2 (PB2) and PA-X], revealed high identities (99.2–99.6%) with the viruses from Lesotho and Botswana and less so with viruses from West Africa. Recently, Clade 2.3.4.4b H5N1 viruses identified in outbreaks in mixed poultry farms in Burkina Faso in December 2021 were shown to be reassortants possessing a PA originating from an H9N2 AIV [ 10 ]. However, the PA from A/Cormorant/Namibia/141/2022 was >99% identical to the PA from the viruses from Lesotho and Botswana and, therefore, the virus is not a reassortant.…”
mentioning
confidence: 99%
“…The subtype of H5, H7, and H9 often occurred at the human–poultry interface . H9N2 was well known for acquiring and sharing genetic material between other flu strains. , Therefore, the subtypes H5, H7, and H9 are most concerning.…”
Section: Introductionmentioning
confidence: 99%
“…2 H9N2 was well known for acquiring and sharing genetic material between other flu strains. 3,4 Therefore, the subtypes H5, H7, and H9 are most concerning.…”
Section: ■ Introductionmentioning
confidence: 99%